SCURT ISTORIC AL EVOLUŢIEI INDUSTRIEI URANIFERE ÎN ROMANIA (PANGEEA, 2025)
ABSTRACT: The evolution of uranium industry in Roumania. Because of the existence in our country of structural conditions favorable geological accumulations of uranium, since 1950, starting a sustainable business, of exploration throughout the country, represented by radiometric measurements of air, land, and mining works in the probe. Also the concept of a nuclear program, aimed at achieving a CANDU nuclear power units, which led to the development activities needed for the exploration, exploitation, processing and capitalization of uranium ore.